Factors of Economic Growth in Sub-Saharan Africa: Current Trends - G. V. Podbiralina (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2018)
Despite the fact that the African continent is positioned as one of the fastest growing economies in the world (especially the sub-region of sub-Saharan Africa), the lack of industrialization and the use of modern technologies continues to be a brake on the development of the economies of African countries, which largely depend on agriculture and exports of raw goods that have a relatively low added value and account for more than 80% of their exports. This has a negative impact not only on the economic development of the region, but also on per capita incomes of the population. This article assesses the existing economic potential of African countries, which is one of the most important factors for overcoming economic backwardness, achieving the goals of sustainable development, raising the standard of living of the population and changing the status of SSA countries in the world economic system. It is shown that it is important for African states to attract new technologies and innovative products to the industrial and agricultural sectors, since knowledge and innovations are the locomotive of economic growth and are one of the most important factors in the reconstruction and modernization of their economies.